Municipal amalgamations in international perspective: motives addressed in scholarly research - Karkin, Naci; Gocoglu, Volkan; Yavuzcehre, Pinar Savas (Asia Pacific Journal of Public Administration)
Mainly underpinned by economic and financial motives, amalgamations of local governments in and beyond municipal areas have often been on the agenda of many governments. Some studies of the amalgamations have aimed to justify them or to falsify the efforts by concentrating on what could alternatively have been achieved; while others have presented the tensions between various dynamics, including democracy and efficiency. The studies have been valuable in identifying numerous factors of significance to amalgamation processes and results. Hence the present analysis of a selected range of them with a particular and important focus on various articulated motives of amalgamation. - Reproduced.
Keywords: Municipal amalgamations